Case report: First isolation of Exophiala dermatitidis from subcutaneous phaeohyphomycosis in a cat - Osada, Hironari; Nagashima-Fukui, Maiko; Okazawa, Taiga; Omura, Miki; Makimura, Koichi; Ohmori, Keitaro (Frontiers in Veterinary Science, 2023)
Phaeohyphomycosis, which is caused by the opportunistic black yeast-like fungus Exophiala dermatitidis, has been reported in humans and dogs. However, no previous studies describing E. dermatitidis infections in cats have been published. Herein, we report a case of subcutaneous phaeohyphomycosis caused by E. dermatitidis. A 12-year-old, castrated male Japanese domestic short-haired cat presented with a solitary subcutaneous abscess on the left side of the neck, where an esophageal tube for force-feeding had been placed previously. The cat was diagnosed with hepatitis and was treated with prednisolone. The subcutaneous abscess was incised using a scalpel blade and the pus was excreted. The cytology of the pus revealed hyphae with neutrophil and macrophage infiltration. Although the cat was treated with oral itraconazole or an infusion of topical ketoconazole cream applied to the lesion, it died. The fungal culture of the pus specimen developed dark-green, waxy, smooth, yeast-like colonies. Sequencing of the internal transcribed spacer 1-4 regions of the ribosomal DNA of the pus specimen showed 100% identity with that of the standard strains of E. dermatitidis. Based on these results, the cat was diagnosed with subcutaneous phaeohyphomycosis caused by E. dermatitidis. The antifungal susceptibility test revealed that the fungus showed low or moderate susceptibility to the antifungal drugs examined, except for amphotericin B, which exhibited high in vitro antifungal activity. This is the first case report to provide definitive evidence of E. dermatitidis infection in cats and antifungal susceptibility test results against clinically isolated E. dermatitidis.